Bahasa dalam Strata Sosial dan Pemikiran Representasinya pada Pembelajaran Bahasa Arab - Ferdiansyah, Novan; Shalihah, Imroatus; Handayani, Latifah; Fikri, Shofil (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2024)
Language and social strata are intertwined in the context of language learning. Then language and mind are two important and interrelated aspects of the human experience. Understanding the complex relationship between language and mind can help us understand the world around us. Therefore, this study aims to investigate how differences in social strata affect the use and understanding of Arabic in learning, as well as how the representation of Arabic in social strata is reflected in language learning. This type of research is qualitative research and the method used is library research by utilizing sources from books, journals, and scientific articles. The results of this study are: (1) differences in social strata can affect the use of Arabic in learning and social strata can also be reflected in Arabic dialect variants; (2) the relationship between language and thought involves a complex interaction between language skills and cognitive processes (3) the representation of thought in Arabic language learning includes listening, reading, speaking, and writing skills in Arabic.